2013
DOI: 10.1152/ajpheart.00042.2013
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine potentiates proatherogenic effects of oxLDL by stimulating and upregulating macrophage CD36 signaling

Abstract: Zhou MS, Chadipiralla K, Mendez AJ, Jaimes EA, Silverstein RL, Webster K, Raij L. Nicotine potentiates proatherogenic effects of oxLDL by stimulating and upregulating macrophage CD36 signaling. Am J Physiol Heart Circ Physiol 305: H563-H574, 2013. First published June 7, 2013 doi:10.1152/ajpheart.00042.2013.-Cigarette smoking is a major risk factor for atherosclerosis and cardiovascular disease. CD36 mediates oxidized LDL (oxLDL) uptake and contributes to macrophage foam cell formation. We investigated a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 62 publications
(78 reference statements)
2
54
0
Order By: Relevance
“…In contrast, the short-term (≤12 weeks) administration of nicotine to animals has been shown to enhance or aggravate existing cardiovascular disease (i.e. chronic hypertension, atherosclerosis, myocardial ischaemia/reperfusion injury) in experimental models (Bui et al 1995; Lau et al 2006; Sridharan et al 1985; Zhou et al 2013). The results of these non-clinical studies suggest the potential for serious cardiovascular adverse effects with nicotine exposure and support the need for a comprehensive review of studies investigating the presence of such SAHE in NRT users.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the short-term (≤12 weeks) administration of nicotine to animals has been shown to enhance or aggravate existing cardiovascular disease (i.e. chronic hypertension, atherosclerosis, myocardial ischaemia/reperfusion injury) in experimental models (Bui et al 1995; Lau et al 2006; Sridharan et al 1985; Zhou et al 2013). The results of these non-clinical studies suggest the potential for serious cardiovascular adverse effects with nicotine exposure and support the need for a comprehensive review of studies investigating the presence of such SAHE in NRT users.…”
Section: Resultsmentioning
confidence: 99%
“…A major role in CS cytotoxicity in A549 cells may be played by acrolein and hydrogen peroxide (Aoshiba and Nagai 2003). Monocytes are more resistant to oxidative stress, but activation of THP1 cells by CS may be mediated by nicotine, which is able to activate immune cells (Zhou et al 2013). It has been shown that antioxidants prevent CS toxicity in A549 cells (Banerjee et al 2008) and decrease protein damage, inflammation, apoptosis, and lung injury in smoke-exposed animals (Rahman 2012), supporting the major role of oxidative stress in CS-induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…4-HNE is a highly reactive and diffusible by-product, which can induce apoptosis, inflammation, emphysema and enlargement of airspaces in COPD [48,49]. Furthermore, oxidation of LDL is also a major risk factor for atherosclerosis and cardiovascular disease [50]. MDA is a carcinogenic product of lipid peroxidation reactions which is found to increase in the sputum of COPD patients (Fig.…”
Section: Arachidonic Acid Metabolismmentioning
confidence: 99%